The Impact of Sauna on Health - Tomasz Dudzik; Łucja Dudzik; Aleksandra Kozieł; Igor Domański (Kazimierz Wielki University, 2024)
This review examines the health implications of regular sauna use, a tradition deeply rooted in Finnish culture now gaining global interest for its potential health benefits. It consolidates findings from various scientific studies, emphasizing the physiological and health impacts of traditional sauna practices on cardiovascular health, mental well-being, and overall mortality. The review highlights the positive cardiovascular outcomes associated with regular sauna use, such as reduced risks of hypertension, coronary artery disease, and sudden cardiac death, attributing these benefits to improved endothelial function, decreased arterial stiffness, and positive changes in blood pressure. Additionally, sauna bathing is shown to offer mental health benefits by reducing stress, depression, anxiety levels, and possibly lowering the risk of neurodegenerative diseases like Alzheimer's and dementia. Despite the substantial benefits, the review also acknowledges potential risks, especially for individuals with specific health conditions, underscoring the importance of hydration and caution against alcohol consumption before sauna sessions. Conclusively, the evidence supports the integration of sauna bathing into health promotion strategies, with a call for further research to explore the mechanisms underlying its health benefits and to develop guidelines for optimizing these benefits while minimizing risks. Sauna bathing emerges as a promising, non-invasive approach to enhancing overall health and well-being, warranting its consideration in complementary health practices.